The role of endothelin-1 in the sympathetic nervous system in the heart - Lehmann, Lorenz; Stanmore, David; Backs, Johannes (Life sciences, 2014)
Endothelin-1 (ET1) is a peptide that was initially identified as a strong inductor of vascular contraction. In the last 25 years, there have been several biological processes identified in which ET1 seems to play a critical role. In particular, genetic studies have unveiled that ET1 is important for neuronal development, growth and function. Experimental studies identified ET1 as a regulator of the interaction between sympathetic neurons and cardiac myocytes. This might be of clinical importance since patients suffering from heart failure are characterized by disrupted norepinephrine homeostasis in the heart. This review summarizes the important findings on the role of ET1 for sympathetic neurons and norepinephrine homeostasis in the heart.